(untitled) (GUB Journal of Science and Engineering, 2024)
The textile industry consumes a lot of water during production and generates a massive amount of effluents, including synthetic dyes, into the environment, which raises public concern. Azo dyes that are predominantly utilized in the textile sector are regarded to offer serious health hazards. Jute sticks are a typical fuel source in Bangladeshi villages. After using jute sticks as fuel, we turn them into highly cost effective activated charcoals which are capable of removing Levafix Amber (most used azo dye) from textile effluent. In this article we reported for the first time a cost effective, ecofriendly jute stick extracted adsorbent for the removal of Levafix Amber dye from textile effluents. The most notable benefits of our approach are its low cost, simplicity, and lack of the need for costly instruments. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 9(1), 2022 P 30-41